La vie mode d’emploi. Graphic and narrative plots (XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2020)
The plot of La vie mode d’emploi, a monumental novel published by Georges Perec in 1978, is intertwined with the life of the young billionaire Percival Bartlebooth, from his youth to the day of his death. However, the real protagonist of the story is the building where Bartlebooth lives: a 10-storey Parisian block with 10 rooms on each floor. Inspired by a drawing by Saul Steinberg, Perec draws a schematic section of the building, arranging each room in a square of a 10 x 10 grid. In this way, from the ground floor to the attics, all the rooms are simultaneously visible. Obviously, the scheme cannot correspond to any real or imaginative building, but it is perfectly topologically consistent. On this grid, Perec develops the narrative plot. Each chapter of the book is dedicated to a room, to the objects it contains and to events that affect its residents. The path followed by the plot is based on several cointraintes, widely used at the OuLiPo (Perec was a very active member of the group): real ‘coercions’, narrative constraints that weave further textures superimposed on the overall design of the story. Ruthless and apparently mechanical rules but, as Italo Calvino observed, Perec’s ultracompleted work intentionally leaves a small opening for incompleteness: when we reach room LXV, the plot slips and we move directly to room LXVII. Room LXVI, located in the lower left corner of the building, remains unexplored. In this way, Perec establishes a parallelism between the narration, the path that winds between the rooms and the ‘unfinished’ life of Percival Bartlebooth: on the verge of death, he cannot insert the last piece of the puzzle to which he had dedicated his whole existence. The entire spatial and narrative framework, in which ‘nothing happens’, seems unfinished, meaningless, tautological, infra-ordinary; but, at the same time, monumental, engaging, impeccable, dizzying. A claustrophobic and boundless space, in which the last hundred years of human history are redesigned with the words and gestures of everyday life.
Keywords: cointrainte; narrative plot; Perec